2018
DOI: 10.1103/physrevb.98.134504
|View full text |Cite
|
Sign up to set email alerts
|

Timing jitter in photon detection by straight superconducting nanowires: Effect of magnetic field and photon flux

Abstract: We studied the effect of the external magnetic field and photon flux on timing jitter in photon detection by straight superconducting NbN nanowires. At two wavelengths 800 and 1560 nm, statistical distribution in the appearance time of the photon count exhibits Gaussian shape at small times and exponential tail at large times. The characteristic exponential time is larger for photons with smaller energy and increases with external magnetic field while variations in the Gaussian part of the distribution are les… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
(67 reference statements)
3
19
0
Order By: Relevance
“…In a theoretical study, the transverse geometric jitter was investigated by considering the variation in detection latency as a function of the transverse location of photon absorption across the nanowire [23]. An experimental study of the jitter associated with meandered [24] and straight [25] nanowires found asymmetry in the jitter profile which was attributed to intrinsic effects, and more recently, an increase in timing jitter was measured in straight NbN nanowires with increasing magnetic field [26] which was qualitatively explained by the hotspot model [15]. The same model is used to study the effects of transverse position dependence on timing jitter [27].…”
Section: Introductionmentioning
confidence: 99%
“…In a theoretical study, the transverse geometric jitter was investigated by considering the variation in detection latency as a function of the transverse location of photon absorption across the nanowire [23]. An experimental study of the jitter associated with meandered [24] and straight [25] nanowires found asymmetry in the jitter profile which was attributed to intrinsic effects, and more recently, an increase in timing jitter was measured in straight NbN nanowires with increasing magnetic field [26] which was qualitatively explained by the hotspot model [15]. The same model is used to study the effects of transverse position dependence on timing jitter [27].…”
Section: Introductionmentioning
confidence: 99%
“…In our present study we evaluate the geometrical contribution to the system jitter in a straight nanowire with the topology similar to the one reported in Ref. [2]. Furthermore, we show that large photon flux reduces drastically the geometrical contribution to the system jitter.…”
Section: Introductionmentioning
confidence: 52%
“…3b shows a typical T + histogram recorded at the lower light intensity and the best fit with the exponentially modified Gaussian distribution described in Ref. [2] .…”
Section: A Triggering Noise Jitter T − and T + Jittermentioning
confidence: 82%
“…Since Superconducting Nanowire Single Photon Detectors (SNSPDs) were introduced in 2001 [1], their performance has been dramatically improved to become the leading technology in single photon detection. Nowadays, SNSPDs offer outstanding performance, with system detection efficiencies of 80 -95 %, from the visible to the infrared [2][3][4][5], dark count rates in the mHz range [5,6], detection count rates up to 1.5 GHz [7], and timing jitter as low as < 10 ps [8][9][10]. High performance SNSPDs operating at 4 K and above, are particularly interesting due to the vast number of potential applications.…”
Section: Introductionmentioning
confidence: 99%